Fostering Better Integration Through Youth-Led Refugee Sponsorship - McKee, Carolyn; Lavell, Lee-Anne; Manks, Michelle; Korn, Ashley (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
World University Service of Canada (WUSC) participates in private sponsorship as a sponsorship agreement holder through its Student Refugee Program. More than ninety campus-based constituent groups known as WUSC Local Committees resettle approximately 130 refugee students to Canadian post-secondary institutions each year. This article seeks to assess the effectiveness of the Student Refugee Program’s youth-to-youth sponsorship model in integrating former refugees into their receiving communities. We outline the impact of the Student Refugee Program upon its beneficiaries, the important role youth volunteers play in supporting their integration and building more welcoming communities for newcomers in Canada, and the effect of the program on receiving societies. We conclude with recommendations for scaling up the program in Canada and sharing the model internationally.